2018
DOI: 10.5811/westjem.2018.1.35630
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use in Pregnant Women Using the Emergency Department: Undertested And Overlooked?

Abstract: IntroductionThe objective was to determine if pregnant women visiting the emergency department (ED) are tested for substance use as frequently as non-pregnant women.MethodsWe captured all ED visits over a six-year period (2010–2016) from a single community hospital and identified women of childbearing age, defined for our study as 11–50 years old. We collected demographic data including age in years, ethnicity, body mass index, marital status, disposition, last encounter department, method of arrival, and day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 13 publications
0
3
1
Order By: Relevance
“…The American College of Obstetrics and Gynecology (ACOG) recommends using a questionnaire to screen all pregnant women regarding drug use, however it does not recommend routine urine drug screens. Despite these recommendations there is existing data that pregnant women presenting to the ED are less likely to be tested for ETOH or drug use than non-pregnant patients 13 which is in direct contrast to our results. Similarly, with regards to Hep C, disappointingly only 47.6% of the non-pregnant and 72.7% of the pregnant patients without known hep C were screened with either Ab or PCR on presentation.…”
Section: Discussioncontrasting
confidence: 99%
“…The American College of Obstetrics and Gynecology (ACOG) recommends using a questionnaire to screen all pregnant women regarding drug use, however it does not recommend routine urine drug screens. Despite these recommendations there is existing data that pregnant women presenting to the ED are less likely to be tested for ETOH or drug use than non-pregnant patients 13 which is in direct contrast to our results. Similarly, with regards to Hep C, disappointingly only 47.6% of the non-pregnant and 72.7% of the pregnant patients without known hep C were screened with either Ab or PCR on presentation.…”
Section: Discussioncontrasting
confidence: 99%
“…The American College of Obstetrics and Gynecology (ACOG) recommends using a questionnaire to screen all pregnant women for substance use disorders. Despite these recommendations, there are existing data that pregnant women presenting to the emergency department are less likely to be tested for alcohol or drug use than nonpregnant patients [ 12 ]. Interestingly, in our study we observed much higher—although suboptimal—rates of urinary drug screening in pregnant patients (82.4% and 50.7%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…This is often the case even among healthcare professionals. A recent study showed that a pregnant woman presenting to an Emergency Department is 75% less likely to be tested for drug use than a non-pregnant woman of similar age [87].…”
Section: Substance Use Disordersmentioning
confidence: 99%
“…Behavioral measures must be the focus of treatment as there is limited data on the use of drugs to treat alcohol dependence (e.g., disulfiram, naltrexone, acamprosate) during pregnancy. Physicians must carefully weigh the risks of using such drugs versus alcohol use [84,87,[94][95][96].…”
Section: Substance Use Disordersmentioning
confidence: 99%